A finite difference-based approach for strain demand prediction of inelastic pipes subjected to permanent ground displacements. (15th December 2022) - Zheng, Qian; Li, Yong; Yoosef-Ghodsi, Nader; Fowler, Matt; Kainat, Muntaseer; Adeeb, Samer
Highlights: Finite difference method can predict pipe's response under the ground movement. Equations of axial force and bending moment are derived involving inelasticity. Finite difference method is of great accuracy for predicting inelastic behaviour. This method can evaluate strain demands of pipes under a wide range of geohazards. Abstract: Permanent ground displacement triggered by geohazards constitutes a major threat to the integrity of long-distance pipelines. In this study, a novel and simple method is proposed to evaluate inelastic pipes' behavior under ground movements considering soil-pipe interaction based on the finite difference method. The existing finite difference-based method previously proposed by the authors for strain analysis of buried pipelines subjected to ground movements excludes material nonlinearity in pipes, which limits its applicability in engineering practice. To remedy this situation, the method presented herein maintains the well-established concepts of the existing finite-difference-based method but also introduces the scheme to consider the inelastic material behavior of steel pipes. More specifically, the expressions of internal axial force and bending moment, required in the finite difference equations, are explicitly derived based on the actual stress distribution on the pipe cross-section. The proposed method is validated against the finite element method (one-dimensional beam model) in terms of the strain and deformation demands using two indicative case studies, referred to as symmetric and non-symmetric soil resistance conditions, respectively. The comparison between finite element analysis and the proposed method indicates good agreement. Additionally, the proposed method is compared with four existing analytical methods for pipes subjected to strike-slip fault displacement. The proposed method is a simple but general technique to analyze pipes' response under a wide range of geohazards, and thus can be potentially used as an alternative method for preliminary design, safety prescreening, and reliability-based assessment of pipes against geohazards.